Determinants of Patent Litigation in Germany - Katrin Cremers (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This paper presents an empirical analysis of the determinants of patent litigation in Germany, based on information from suits filed during the period from 1993 to 1995 at two of the three most important district courts. A control group was formed by selecting a random sample from the population data taken at this period of time. The results of a probit analysis show that relatively valuable patents are more likely to be involved in litigation cases than the average patent. Patents which have survived opposition are more likely to encounter subsequent litigation actions after the granting procedure than patents which have not been opposed. Patent owner?s ability to trade patents with potential infringers and to interact with them repeatedly appears to promote pretrial settlement and to prevent patentees from filing suits. In contrast to results for the U.S., individual patent owners in Germany were found to be no more likely to face litigation than companies.
Keywords: K41; O34; 330; Patent; Infringement; Litigation; Innovation; Patentrecht; Zivilprozess; Patent; Innovation; Schätzung; Deutschland